KEPUTUSAN TRANSFER PRICING : PENGARUH BEBAN PAJAK, KONTRAK UTANG, DAN PROFITABILITAS: TRANSFER PRICING DECISIONS: THE EFFECT OF TAX EXPENSE, DEBT CONTRACTS, AND PROFITABILITY - Mulyani, Dinda; Pahala, Indra; Nasution, Hafifah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
Transfer pricing is the practice of determining the price of goods, services, or assets transferred from one company to another company that has a linkage or special relationship. Transfer pricing can be done either by affiliated companies integrated under the same management or by different companies but have a special relationship, both at the domestic and international levels. The aim of this research is to test the influence of tax burdens, debt contract, and profitability on transfer pricing decision in energy sector companies that listed at Indonesia Stock Exchange. Sample selection was using purposive sampling with final sample 19 companies and 57 observation from 2020-2022. This research uses panel data regression analysis. The choice of this technique is because the research data is a panel that combines cross section and time series data types. The tool used to support data analysis in this study is Eviews software. The result shows that tax burdens have an influence on transfer pricing decision, while debt contact and profitability have not influence on transfer pricing decision. This is due a business decision driven by impact of the COVID-19 pandemic that cause the economy collapse